Randomized Phase II Trial of Vincristine-Irinotecan With or Without Temozolomide, in Children and Adults With Relapsed or Refractory Rhabdomyosarcoma: A European Paediatric Soft Tissue Sarcoma Study Group and Innovative Therapies for Children With Cancer Trial. Issue 27 (20th September 2021) - Defachelles, Anne-Sophie; Bogart, Emilie; Casanova, Michela; Merks, Johannes H. M.; Bisogno, Gianni; Calareso, Giuseppina; Gallego Melcon, Soledad; Gatz, Susanne Andrea; Le Deley, Marie-Cécile; McHugh, Kieran; Probst, Alicia; Rocourt, Nathalie; et al.
Abstract : PURPOSE: The VIT-0910 trial was conducted to evaluate efficacy and safety of the vincristine-irinotecan combination with and without temozolomide (VIT and VI, respectively) in relapsed or refractory rhabdomyosarcoma (RMS). METHODS: In this randomized European phase II trial, patients age 0.5-50 years received 21-day cycles combining vincristine (1.5 mg/m 2 once a day on day 1 and day 8) and irinotecan (50 mg/m 2 once a day from day 1 to day 5) with and without temozolomide (125 mg/m 2 once a day from day 1 to day 5 and 150 mg/m 2 once a day from cycle 2), until progression or unacceptable toxicity. The primary end point was objective response rate after two cycles. Secondary end points included best response, progression-free survival, overall survival, and adverse events. A Simon 2-stage design was initially planned to separately analyze 40 patients/arm. After amendment, the trial sample size was increased to 120 and a comparison between arms, adjusted for confounding factors, was added to the statistical plan (ClinicalTrials.gov, NCT01355445 ). RESULTS: Overall, 120 patients (60 per arm) were recruited in 37 European centers. The median age was 11 years (range, 0.75-45); 89% of patients had a relapsed RMS. The objective response rate was 44% (24 of 55 evaluable patients) for VIT versus 31% (18 of 58) for VI (adjusted odds ratio, 0.50; 95% CI, 0.22 to 1.12; P = .09). The VIT arm achieved significantly better overall survival (adjusted hazard ratio, 0.55; 95% CI, 0.35 to 0.84; P = .006) compared with VI, with consistent progression-free survival results (adj-hazard ratio, 0.68; 95% CI, 0.46 to 1.01; P = .059). Overall, patients experienced adverse events ≥ grade 3 more frequently with VIT than VI (98% v 78%, respectively; P = .009), including a significant excess of hematologic toxicity (81% v 61%; P = .025). CONCLUSION: The addition of temozolomide to VI improved chemotherapy efficacy for patients with relapsed RMS, with manageable increase in toxicity. VIT is considered the new standard treatment in these patients in the European paediatric Soft Tissue Sarcoma Group and will be the control arm in the next randomized trial.